Effect of Financial Development on the Transmission of Monetary Policy - Seth, Rama; Kalyanaraman, Vaanchitha (Scientific Research, 2017)
This paper looks at the effect of financial development on output and bank liquidity by doing a cross-country analysis of 119 countries across 18 years from 1997-2014. We develop three hypotheses by combining multiple strands of literature which have heretofore existed in parallel. The main research question is whether financial development serves to provide greater bank liquidity and whether it does indeed stimulate output growth. This question is of particular relevance when there are changes in monetary policy. This paper goes to the heart of examining whether monetary policy is transmitted more effectively with better financial development and whether the goal to achieve output changes via monetary policy is better effected in an environment of developed financial markets. Our results support the hypotheses that financial development positively impacts output, and negatively affects bank liquidity. We also show that with financial development, the effect of bank liquidity on output is heightened.
Keywords: Monetary Policy; Financial Development; Money Supply; Bank Liquidity; Output